IL-37 inhibits the production of pro-inflammatory cytokines in MSU crystal-induced inflammatory response. Issue 9 (September 2016) - Zeng, Mei; Dang, Wantai; Chen, Baofeng; Qing, Yufeng; Xie, Wenguang; Zhao, Mingcai; Zhou, Jingguo
Abstract Acute gouty arthritis (AGA) is an auto-inflammatory disease characterized by resolving spontaneously, which suggests that negative feedback loops control inflammatory and immunological responses to monosodium urate (MSU) crystals. By now, the molecular mechanism for spontaneous resolution of acute GA remains unclear; this study was undertaken to evaluate whether IL-37 is involved in spontaneous resolution of AGA. A total of 45 acute GA (AGA), 29 non-acute GA (NAGA) male patients and 82 male health control (HC) were involved in this study, we measured IL-7 expression in the peripheral blood mononuclear cells (PBMCs), together with levels of IL-1β, IL-6, IL-10, TNF-α and TGF-β1 in the serum. Further, we either inhibited IL-37 expression in human PBMCs with siRNA or over-expressed the cytokine in human macrophages. Pro-inflammatory cytokine IL-1β, IL-6, and TNF-α expressions were significantly higher in the AGA group than in the NAGA or HC group (P < 0.05, respectively). However, anti-inflammatory IL-37, TGF-β1, and IL-10 were greater in the NAGA group than in the AGA and HC groups (P < 0.05, respectively). Expression of IL-37 in MSU crystal-treated macrophages inhibited the expression of pro-inflammatory cytokines, whereas the abundance of these cytokines increased with silencing of endogenous IL-37 in human blood cells. However, anti-inflammatory TGF-β1 and IL-10 expressions in these supernatants were unaffected by over-expression or knockdown of IL-37. Our study indicates that IL-37 is an important anti-inflammatory cytokine in AGA by suppressing the production of pro-inflammatory cytokines. Thus, IL-37 may provide a novel research target for the pathogenesis and therapy of GA.